Precision-engineered mRNA vaccines: antigen design, structural optimization, and programmable delivery for emerging pathogens - Yanyu Zhang; Junchi Li; Zihan Wang; Yu Kuang; Songli Li; Xiaojia Wang (Animal Diseases)
Abstract The rapid evolution of pathogen threats and pandemic risks has intensified the demand for adaptable vaccine platforms with rapid design-to-clinical timelines. The success of BNT162b2 and mRNA-1273 in controlling COVID-19 has led to unprecedented changes in vaccine development. Compared with traditional platforms, mRNA vaccines offer distinct advantages: avoiding genomic insertion risks of DNA vaccines; facilitating rapid, scalable production via in vitro transcription; and enabling new modular antigen design against evolving pathogens. However, the development of mRNA vaccines for infectious diseases still faces challenges, including structural stability, translation efficiency, and targeted delivery. This review presents cutting-edge strategies for designing antigens, optimizing mRNA structural elements, and optimizing delivery systems to target infectious pathogens. This study provides a detailed explanation of antigen optimization strategies for different types of mRNA vaccines and explores the potential applications of broad-spectrum and combination mRNA vaccines in human and animal pathogens. Finally, we address the current challenges and future prospects of mRNA vaccine technology, aiming to inform and accelerate the development of next-generation vaccines against emerging pathogens through the integration of these innovations.